3D printed PC/SiOC@Zn hybrid composite as dendrite-free anode for Zn-Ion battery. (September 2022) - Idrees, Muhammad; Batool, Saima; Cao, Jiwei; Javed, Muhammad Sufyan; Xiong, Shufeng; Liu, Changyong; Chen, Zhangwei
Abstract: Zinc-ion batteries (ZIBs) have been considered a key competitor in energy storage devices due to their abundant reserves, low cost, and intrinsic safety. However, their uncontrollable dendritic growth and parasitic reactions hampered their commercial rejuvenation. Here, 3D printed electrode with a novel hybrid PC/SiOC composite material is designed to regulate zinc-ion deposition and control dendrites formation. Significantly, the interpenetrated SiOC network within a porous carbon not only improves conductivity and active sites but also guides the uniform nucleation of Zn 2+ in porous carbon voids. With such tuned surface wettability and electronic features, the 3DP-PC/SiOC@Zn anode in half-cell achieves a superior capacity of 99 mAh g −1 at 0.45 A g −1, while in the symmetric cell, it demonstrates impressively low and stable voltage polarization at 10 mA cm −2 for 800 h of operational lifespan, revealing a high Zn plating/stripping process. The 3DP-PC/SiOC@Zn anode coupled with a V2 O5 /C cathode as a full battery exhibits a high capacity of 67 mAh g −1 at 0.5 A g −1 . The developed electrohealing extends the battery's lifespan to 46 and 23.8 h at 10 and 15 mA cm −2 . This elaborated study introduces a 3DP electrode based on a novel hybrid PC/SiOC composite to develop dendrite-free ZIBs. Graphical Abstract: A novel hybrid UiO-66-NH2/PDSDA composite is synthesized using a conventional polymerization method, followed by pyrolysis to produce a hybrid PC/SiOC composite anode material, which is then rationally designed into a 3DP-PC/SiOC@Zn anode. The as-fabricated 3DP-PC/SiOC@Zn as dendrite-free anode's improved performance is primarily due to the interpenetrated SiOC network and 3D printed grid structure. ga1 Highlights: 3D printed hybrid PC/SiOC@Zn composite anode has been designed. Optimized 3D grid structure of electrode quickly reverse, host, and guide Zn 2+ . Improved active sites and surface area strengthens the rapid Zn plating/stripping process. The SiOC network regulates Zn 2+ flux and controls dendrites to ensure uniform Zn-ion deposition. The developed electrohealing process greatly extends the lifespan of Zn-Ion batteries.